Pengaruh Kinerja Keuangan dan Ukuran Perusahaan terhadap Pengungkapan CSR pada Perusahaan Bumn yang Listed di BEI Periode 2012-2017 - Novi Yanti; Nova Begawati (SAFE-Network, 2023)
This study aims to determine the effect of financial performance and company size on CSR disclosure either partially or simultaneously. This research was conducted at state-owned companies listed on the Indonesia Stock Exchange in the period 2012-2017. The population in this study are all BUMN companies listed on the Indonesia Stock Exchange (IDX) for the period of 2012-2017 as many as 20 companies. The number of companies sampled in this study were 14 companies during the study period, from 2012-2017 using the purposive sampling metho The analytical method used is multiple linear regression analysis and the coefficient of determination. Hypothesis testing uses the t test and the F test. The results showed that: 1. Financial performance had a positive and significant effect on the disclosure of CSR of BUMN in the 2012-2016 period. 2. The size of the company has a positive and significant effect on the disclosure of CSR of BUMN in the 2012-2016 period. 3. The contribution of financial performance and company size to CSR disclosures is 43.9% while the remaining 56.1% is influenced by other variables such as managerial ownership, institutional ownership, leverage and others.